Consumer Protection in Payment Order Proceedings - Sirvydytė, Monika (Teisė, 2025)
An order for payment is one of the simplest ways to recover uncontested debts. While the formal nature of this simplified procedure allows for the swift and effective protection of creditors’ rights, it may also lead to violations of debtors’ rights, particularly those belonging to vulnerable groups. This article examines the specific features of payment orders against consumers. The article aims to systematize and analyze the case law of the Court of Justice of the European Union (CJEU) and identify the EU law requirements that apply to such procedures. The article also evaluates the impact of the case law of the CJEU on national civil procedure systems. The analysis reveals that the CJEU interprets the principle of effectiveness differently in relation with payment procedures, depending on whether the procedure is based on documentary evidence. Furthermore, the Court’s interpretation of the level of consumer protection within the European order for payment procedure remains legally ambiguous. The findings demonstrate that the Court’s decisions cause significant fragmentation of national civil procedures and generate legal uncertainty in civil procedural law.